2014 IEEE 20th International Symposium on High Performance Computer Architecture (HPCA) 2014
DOI: 10.1109/hpca.2014.6835969
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic management of TurboMode in modern multi-core chips

Abstract: Dynamic overclocking of CPUs, or TurboMode, is a feature recently introduced on all x86 multi-core chips. It leverages thermal and power headroom from idle execution resources to overclock active cores to increase performance. TurboMode can accelerate CPU-bound applications at the cost of additional power consumption. Nevertheless, naive use of TurboMode can significantly increase power consumption without increasing performance. Thus far, there is no strategy for managing TurboMode to optimize its use across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…However, recent work has shown that these schemes are unsuitable for latencycritical applications since they focus on long-term performance and severely hurt tail latency [24,33,34,39].…”
Section: Dynamic Power Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work has shown that these schemes are unsuitable for latencycritical applications since they focus on long-term performance and severely hurt tail latency [24,33,34,39].…”
Section: Dynamic Power Managementmentioning
confidence: 99%
“…HW-T and HW-TPW are hardware-controlled schemes that perform coordinated per-core DVFS: HW-T sets frequencies to maximize aggregate system throughput (IPC) while staying below TDP; HW-TPW maximizes aggregate throughput per watt. These schemes adapt every 100 µs, and represent hardware-controlled DVFS schemes typical of modern chips (e.g., Turbo Boost [34,46]). All schemes use a partitioned memory system.…”
Section: Rubikcoloc Evaluationmentioning
confidence: 99%
“…Energy proportional computing: Energy proportional computing have been a major area of research [1], [5], [6], [9], [15], [18], [35]- [37]. In addition, measurements, metrics and trends of energy proportionality have all been well studied [19], [21], [22], [35], [38].…”
Section: Related Workmentioning
confidence: 99%
“…Active low power modes, on the other hand, remains effective even with multi-core scaling [8], [18]. Commercially available active low power modes includes DVFS [5], where the processor's voltage and frequency are scaled down as the server's workload decreases. While this work does not explore component and server-level energy proportionality techniques, it does rely on high energy proportional servers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation